2014
DOI: 10.1111/ijd.12690
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled clinical trial on the efficacy and safety of 3% Rumex occidentalis cream versus 4% hydroquinone cream in the treatment of melasma among Filipinos

Abstract: Rumex occidentalis 3% cream is a safe and effective skin-lightening agent for melasma and is comparable in efficacy with 4% HQ cream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…Few studies were excluded as full text were not available. Finally, 11 studies, including 9 randomized controlled trials (RCTs), were evaluated that used 4% HQ among 735 subjects[ 22 23 24 25 26 27 28 29 30 31 32 33 ] [ Table 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies were excluded as full text were not available. Finally, 11 studies, including 9 randomized controlled trials (RCTs), were evaluated that used 4% HQ among 735 subjects[ 22 23 24 25 26 27 28 29 30 31 32 33 ] [ Table 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A single study reported lesser efficacy when compared to 3% rumex occidentalis[ 28 ] (LOE-2) and 1% flutamide[ 29 ] (LOE-2). No further studies substantiated these findings however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formulation was applied twice a day for a period of 8 weeks, with examinations every 2 weeks using a Mexameter ® system. The results indicate that while similar declines in skin pigmentation were observed for both 3% sorrel extract and 4% hydroquinone, sorrel extract proved to be a safe and effective means of lightening discoloration in melasma …”
Section: Discussionmentioning
confidence: 96%
“…So wurde z. B. für Rumex occidentalis in einer doppelblind durchgeführte Studie gezeigt, dass es bei Melasma eine vergleichbare Wirkung zu Hydroquinone aufweist . Bei Aphten scheint ein Extrakt aus Alhagistrauch eine Wirkung zu erzielen – ebenfalls getestet in eine doppelblind Studie .…”
unclassified